Realisasi Pertukaran Giliran Bicara dalam Pembelajaran Tematik Kelas IV Pendekatan Student Centered Approach - Shofi Alfinda Ayu Rahmawati; Gigit Mujianto (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to describe the structure of turn-taking used by students and students, as well as classroom activities, with the application of a student-centered approach. This research is descriptive qualitative research. The data sources in this study are two voice recordings of students' and students' speeches in the Teaching Campus activities of the 3rd batch of placements at SD Negeri Dolopo 2 Madiun Regency. The data collection technique used in this research is the listening-recording technique. The results showed that, first, in the learning process of students and students, there were four structures of turn-taking exchange, including; (1) direct management speech, (2) indirect management speech, (3) direct discipline requests, and (4) verbal reactions. Second, this study found active learning activities using a student-centered approach. The active learning activities are; (1) the teacher divides the students into several small groups, (2) the teacher gives topics that each group will discuss, (3) in groups, students discuss the topics that have been given, and (4) students present the results of group discussions.